Low-profile flexible frequency-reconfigurable millimetre-wave antenna for 5G applications. (3rd August 2018) - Jilani, Syeda Fizzah; Rahimian, Ardavan; Alfadhl, Yasir; Alomainy, Akram
Abstract: This paper presents the design and characterisation of a flexible, inkjet-printed, low-profile, and frequency-reconfigurable antenna, intended for the fifth generation (5G) wireless networks operating at millimetre-wave (mm-wave) frequency bands. The antenna geometry is comprised of a slotted T-shaped radiating patch embedded in a rectangular aperture cut inside the ground plane. The slots are designed with two pairs of switches to reconfigure the radiating area for the desired selection of operating frequency at the Ka -band (26.5–40 GHz). Moreover, a two-element inkjet-printed multiple-input multiple-output (MIMO) antenna assembly is proposed based on a flexible polyethylene terephthalate film. The conformal MIMO antenna is suitable for integration in high-performance flexible 5G front-ends, as well as in next-generation wearable electronic devices and applications.